Behavior of the muscle strength and arm muscle area during 24 weeks of weight training - Alexandre Hideki Okano; Edilson Serpeloni Cyrino; Fábio Yuzo Nakamura; Débora Alves Guariglia; Matheus Amarante Nascimento; Ademar Avelar; Antonio Carlos de Moraes (Revista Brasileira de Cineantropometria e Desempenho Humano, 2008)
The purpose of this study was to analyze the behavior of muscle strength and arm muscle area (AMA) over24 weeks of weight training (WT) as well as to establish possible associations between these variables. The sample wascomposed of 18 men aged between 18 and 30 years. Measurements of relaxed arm circumference and triceps skinfoldmeasurement were used for the calculation. Muscle strength was assessed using the one-repetition maximum test (1-RM)on the arm curl exercise. The WT protocol lasted 24 weeks, divided into 3 stages (F1, F2, and F3) of 8 weeks each. It isimportant to emphasize that every measurement was made before, during and after the end of the WT period. Analysis ofvariance (ANOVA) for repeated measures followed by the Tukey post hoc (P < 0.05) was used to the compare the indicatorsof muscle strength and muscle hypertrophy. Pearson’s correlation coefficient was used to verify possible association betweenmuscle strength and AMA. Muscle strength and AMA increased continuously throughout the whole period except for theinitial period (F1). Therefore, it is concluded that the initial phase of training, neuromuscular adaptation, seems to havebeen the turning point for increase in muscle strength. After that, the hypertrophy process appears to gradually become theessential factor for increase in muscle strength.